Analisis keterampilan mengajar guru mengadakan variasi pada pembelajaran tematik sekolah dasar - Anindita Ulya Rahmah; Sandra Bayu Kurniawan; Tri Budiharto (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2022)
This study aims to describe the skills of teachers, find out the obstacles faced, and how to overcome the obstacles faced by teachers at elementary school conducting variations on thematic learning. The research subjects were teachers from grades I to VI. This research is descriptive qualitative research with a case study approach. The research subjects were teachers and students. Data collection techniques used consisted of observation, interviews, and documentation. Validity of the data was used using triangulation techniques. The data analysis technique used is the interactive data analysis model by Miles and Huberman. The results of this study indicate that the teacher has carried out the activities of conducting variations although there are still obstacles. Each teacher has implemented the use of a clear and fluent voice, made eye contact with students, used media and student involvement in its use, as well as patterns of interaction between teachers and students. The obstacle experienced is that they have not been able to use varied media such as concrete media. Teachers use LCD more often because of limited time for learning. So it shows that in the use of media and teaching tools, teachers at SD Negeri Setono are still relatively low.